1969
DOI: 10.1063/1.1664992
|View full text |Cite
|
Sign up to set email alerts
|

Mth Power of an N × N Matrix and Its Connection with the Generalized Lucas Polynomials

Abstract: The Mth power of an N x N matrix is expressed via the Cayley-Hamilton theorem as a linear combination of the lower powers of the matrix. The polynomial coefficients of the lower powers of the matrix are expressed in terms of polynomials in N variables, termed the generalized Lucas polynomials. The independent variables in the generalized Lucas polynomials are the traces of the lower powers of the matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The solution (2) is easily obtained by noticing that Proof. The first formula in (7) follows from direct substitution of D(t) into the given equation (1). The relations (6) are verified by induction [11], The second summation in (7) is then immediate from (6).…”
mentioning
confidence: 99%
“…The solution (2) is easily obtained by noticing that Proof. The first formula in (7) follows from direct substitution of D(t) into the given equation (1). The relations (6) are verified by induction [11], The second summation in (7) is then immediate from (6).…”
mentioning
confidence: 99%
“…., r, and therefore of the generalized Lucas polynomials (in r variables) k-1 E Fg,n+r-g-1 (I1,''' Ir)Z n= Various papers have been devoted to the study of the above polynomials (see [21]) and to the extension of the algebraic theory of the Lucas numerical functions (see, e.g., [133, [22]). 1 The functions Fl.n(I1,'", L), n--1, are called in the literature generalized Lucas polynomials (see [2], [21]). The above results have been extended (see [4]) to a matrix whose minimal polynomial is known.…”
Section: An Explicit Formula For F() and The Generating Functions Of mentioning
confidence: 99%
“…(3) is to note that Hn(n;;' 3) can be written as a linear combination of H2, H, and I by virtue of the Cayley-Hamilton theorem. The coefficients of these matrices are polynominals in the three eigenvalues of H. Barakat and Baumann (1969) have shown that these polynomials are expressible in terms of generalized Lucas polynomials, a class of functions they introduced to study the Mth power of an N x N matrix. They show that…”
mentioning
confidence: 98%